Elastic Settlement Analysis for Various Footing Cases Based on Strain Influence Areas - Pantelidis, Lysandros (My University, 2020)
In the present paper, the strain influence area method is introduced, which, technically, is classified between the classical elastic theory and Schmertmann’s semi-empirical method for immediate settlement analysis, exploiting the advantages of both. Strain influence area values are given in chart form for the calculation of elastic settlement at various locations on the plan view of flexible circular and rectangular footings, embankment loadings as well as for circular rigid footings on sands and clays. Among the major advantages of the proposed method is the direct and convenient calculation of the water table correction factor through the same charts; as known when the water table rises into the influence zone, the soil stiffness reduces, thus, additional settlement is induced. Finally, a new correction factor related to the effect of footing load on the modulus of elasticity of sands is proposed, whilst the Terzaghi’s empirical formula giving the effect of footing shape on the modulus of elasticity of soils has been revisited. It is very interesting that this empirical correction seems to cancel out the adverse effect of the second dimension of footing on elastic settlement analysis.
Keywords: Cone penetration test; Elastic settlements; Immediate settlement analysis; Schmertmann’s method; Strain influence factor; Water table correction factor